Bacteriological and compositional analysis of bovine milk from four municipalities of the department of Putumayo, Colombia - Flórez Delgado, Dixon Fabián; Cely Leal, Dubel Reinaldo; González, Sthefany Daniela; Niño Vera, Lady Johana; Robledo Palomino, Yoicy (Spei Domus, 2024)
The bacteriological and compositional quality of raw bovine milk has very important economic and health implications for the agricultural development of the country. The aim of this research was to analyze raw bovine milk bacteriologically and compositionally from dual-purpose livestock production systems in the municipalities of Puerto Asís, Villagarzón, Orito and Valle del Guamuez in the department of Putumayo. For this, intentional sampling was used in 250 livestock farms, thus obtaining 854 milk samples. The parameters of somatic cells (cs/mL), aerobic mesophilic bacteria count (cfu/mL), fat, protein, lactose, and total solids were analyzed. The data obtained were subject to analysis of variance with a significance of 5%. A difference was evident for the parameters of fat and total solids between the municipalities. When analyzing the results with respect to the ntc 399 raw milk standard, the parameters of somatic cells, mesophilic bacteria, protein, lactose, and total solids are met in the four municipalities. For its part, the fat parameter is met in Puerto Asís and Valle del Guamuez.
Keywords: Mesophilic Bacteria; Somatic Cells; Fat; Milk Production